(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes effective methods of using Uzbek children’s folklore in primary school reading lessons. During the study, the impact of interactive methods, game technologies, staging and multimedia tools on the effectiveness of education was studied. The results of the experiment showed that lessons based on folklore increase the level of students’ mastery.